The Wiley handbook of educational policy - Papa, Rosemary; Armfield, Shadow W. J. (Wiley Blackwell, 2018)
Illuminates the multiple barriers that plague the education system and shows the way toward enlightened and inclusive educational policy and policymaking This book showcases new scholarship in the broad field of education policy and governance. Authored by some of the field's foremost scholars, as well as new and up-and-coming academics, this definitive handbook offers a range of cultural, economic, and political perspectives on the state of education policy today. It addresses historic, current, and future education policy-incorporating changing social landscapes of education, economy, and policy. The Wiley Handbook of Educational Policy covers the role of politics in education governance; the politics of philanthropy and for-profits; the culture and economy of professional organizations; the governance of technology integration; and future political realities to global citizenry. Themes and topics range not only across early childhood, K-12, and tertiary forms of schooling, but also across the policy questions and concerns that transcend these distinctions. Each chapter features key words, key questions, conclusions, and thought-provoking ideas that provoke readers to think about ways to improve the current conditions under which educational policy-makers work.-Provides a traditional understanding of educational policy -Shows how educational policy has changed due to the boom of private funding -Explores the changing demographics in education populations over the last 40 years -Discusses policies and the ethics of using and overseeing technology in teaching and learning environments -Looks at future trends from contemporary political origins The Wiley Handbook of Educational Policy is an important book that should be read by every administrator, policy maker, and educator working in the education system.- Resumé vydavatel